Поетико-виражальні засоби весільних пісень Західного Полісся - Пикалюк, Лілія; Pykaliuk, Liliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджується поетико-виражальна система західнополіських весільних пісень. Проведений у роботі аналіз дає змогу розширити розуміння мовно-культурного комплексу українців, пізнати семантику основних весільних обрядодійств, атрибутів та образів.The article examines the poetic and expressive system western Polissya wedding songs. Conducted in the analysis allows us to expand the understanding of language and cultural complex Ukrainian, learn basic semantics of sacred ceremonies wedding, attributes and images. Based on the analysis of texts wedding songs from established that the use of poetic means of expression caused by functional feature directing genre varieties of wedding songs. With established that artistic language song texts marked by high emotion, wit, particularly phonics and rich text texture trails, stylistic figures that are designed to emphasize the power of expression in the song of sorrow, joy, fear and other emotions. The sending paper is based on attracting a wide factual material, including archival funds that enabled objective conclusions.
Poetiko-expressive Facilities of Weddings Songs of Western Polissia
Keywords: Західне Полісся; весільні пісні; поетика; тропи; стилістичні фігури; Western Polissia; wedding songs; poetics; tropes and stylistic figures